Dynamics of Police, Prosecutor, and Court Collaboration in Online Data Storage and Case Filing - Prayuda, Hendry; Sobri, Kgs M.; Sriati, Sriati; Putra, Raniasa (Universitas Medan Area, 2024)
This research explores the dynamics of collaboration between the Police, Prosecutors, and Courts in the context of data storage and case filing moving to an online format. The growth of information technology has driven this shift, but implementation has not always been smooth. Through a process analysis approach, this research aims to uncover the factors that influence such collaboration and its impact on the efficiency and success of law enforcement. The research methods used include case studies, surveys, and qualitative data analysis. The results highlighted the challenges and barriers faced in the implementation of the online-based system, including technical, legal, and organizational culture aspects. Based on the results of the analysis, the author concludes the need to develop a more efficient and adaptive collaboration model to support digital transformation in law enforcement in the modern era, considering the complexity and dynamics of inter-agency relationships.